Study on multi-objective optimization for nuclear reactor radiation shield design coupling genetic algorithm with paralleling discrete ordinate code - Liu, Bin; Tan, Yi; Jing, Futing; Hu, Guang; Yan, Mingfei (Frontiers in Energy Research, 2022)
An optimization method combining a genetic algorithm and the paralleling discrete ordinate code is developed and applied to the shielding design of the Savannah reactor. Several approaches are studied to cope with the multi-objective optimization problem, such as transforming into single-objective optimization approach, non-dominated sorting approach, and the approach of adding constraints on sub-objectives. Comparing with the current design methods, the optimization method developed in this study shows better performance since the discrete ordinate calculations are free of statistical fluctuations. The multi-objective optimization approach with constraints on sub-objectives seems to have the best performance. More optimized individuals satisfying the constraints can be obtained, and the optimized objectives show the best improvements comparing with the initial design.